DISTRIBUTION OF NOSTOC ELENK SPECIES (Academicia Globe: Inderscience Research, 2021)
In this article, we have analyzed and summarized the data on the distribution of Nostoc Elenk species in Central Asia.According to “Algae” (Kiev, 1989), when it is announced that the species of the Nostoc family consists of 14, J. Komarec (Komarec et al., 2008) stated that it consists of 25 taxa. Among them, benthos, epiphytes, that is, those that spread on the bark of tree trunks, epiliths, that is, on the surface of rocks, and those that spread on the surface of slightly polluted water bodies and soils.